2021
DOI: 10.1021/acs.estlett.0c01013
|View full text |Cite
|
Sign up to set email alerts
|

Improved LC–MS/MS Method for the Simultaneous Determination of Synthetic Phenol Antioxidants and Relevant Metabolites Making Use of Atmospheric Pressure Chemical Ionization and a Trap Column

Abstract: The prevalently used LC–MS/MS methods for the simultaneous determination of synthetic phenol antioxidants (SPAs) and relevant metabolites suffer from a serious drawback of low sensitivity for 2,6-di-tert-butyl-4-hydroxytoluene (BHT) and a common issue of background contamination, which hampers the simple and accurate detection of these substances at trace levels in environmental samples. In this study, we developed an improved LC–MS/MS method for the simultaneous determination of eight SPAs and four relevant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…Previous studies have identified high concentrations of AOs in plastic-containing products. , A recent study using nontargeted analysis identified AO168 and tris­(2,4-di- tert -butylphenyl) phosphate (AO168O) in face masks . Although previous studies have identified some AOs in both human matrices (urine, , serum, , milk, and fingernails) and environmental ones (indoor dust, air particulates, , sludge, , soil, sediment, and water), there is very little information about whether single-use face masks may act as a source of AOs. In this study, we selected as target chemicals 15 SPAs, five OPAs, and five corresponding OPA oxidation products that have previously been detected in commercial products and environmental matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified high concentrations of AOs in plastic-containing products. , A recent study using nontargeted analysis identified AO168 and tris­(2,4-di- tert -butylphenyl) phosphate (AO168O) in face masks . Although previous studies have identified some AOs in both human matrices (urine, , serum, , milk, and fingernails) and environmental ones (indoor dust, air particulates, , sludge, , soil, sediment, and water), there is very little information about whether single-use face masks may act as a source of AOs. In this study, we selected as target chemicals 15 SPAs, five OPAs, and five corresponding OPA oxidation products that have previously been detected in commercial products and environmental matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Because synthetic antioxidants are not covalently bonded to polymeric materials, their release from polymers into the ambient environment can easily occur during the production, use, recycling, and disposal of these polymeric products. , A series of previous studies identified the environmental occurrence of and human exposure to multiple low-molecular weight (LMW) SPAs . These LMW SPAs, as exemplified by 2,6-di- tert -butyl-hydroxytoluene (BHT), have been widely detected in various environmental media (air, dust, soil, water, sediment, and sludge) and human specimens (blood, breast milk, urine, and fingernail), which revealed a picture of widespread environmental pollution and exposure to these LMW SPAs.…”
Section: Introductionmentioning
confidence: 99%
“…2,30 The LC−MS/ MS system consisted of ExionLC AC ultrafast LC interfaced with a Triple Quad 5500 mass spectrometer (…”
mentioning
confidence: 99%